Pregnancy outcome after a first episode of cerebral vein thrombosis. (12th October 2016) - Martinelli, I.; Passamonti, S. M.; Maino, A.; Abbattista, M.; Bucciarelli, P.; Somigliana, E.; Artoni, A.; Gianniello, F.; Peyvandi, F.
Abstract : Essentials Little is known about recurrences and pregnancy outcome after cerebral vein thrombosis (CVT). We studied a cohort of pregnant women with CVT. Women with CVT appear at increased risk of late obstetrical complications despite prophylaxis. Risks of recurrent thrombosis and bleeding in women on heparin prophylaxis while pregnant are low. Summary: Background: The risk of recurrent thrombosis and bleeding episodes in women with previous cerebral vein thrombosis (CVT) on antithrombotic prophylaxis with low‐molecular‐weight heparin (LMWH) during pregnancy is not established and little information is available on pregnancy outcome. Objectives: The aims of this study were to evaluate the risk of obstetrical complications, recurrent venous thrombosis and bleeding in a cohort of pregnant women on LMWH after a first episode of CVT. In addition, to estimate the relative risk of obstetrical complications, patients were compared with healthy women without thrombosis and with at least one pregnancy in their life. Patients: We studied a cohort of 52 patients and 204 healthy women. Results: The risk of developing late obstetrical complications was 24% (95% CI, 18–38%), leading to a relative risk of 6.09 (95% CI, 2.46–15.05). The risk of miscarriage was not increased. The higher risk of late obstetrical complications in patients appeared unrelated to a previous history of obstetrical complications, to the carriership of thrombophilia abnormalities, or to the presence of co‐morbidities. The incidence of termination observed in patients with thrombophilia was double that observed in those without. No recurrent thrombosis or bleeding episodes were observed. Conclusions: Women with previous CVT on LMWH prophylaxis during pregnancy have a low risk of developing recurrent thrombosis or bleeding episodes, but seem to have an increased risk of late obstetrical complications.